Contributions of Ibn Al-Haytham on optics - Yunus, Nurul Azhani; Ismail, Ahmad Faris (IIUM Press, 2011)
The objective of this cpapter is to explore optics in view of Ibn Haytham's work on optics.The methodology adopted is based on data collected from articles, journals and books. This chapter investigates the contribution of Ibn AI-Haytham in optics and related fields. Moreover, the main focus of this chapter is to discuss optics theory by Ibn AlHaytham.nThe significance of this is that it provides knowledge on optics theory based on Ibn Haytham's work